2019
DOI: 10.1016/j.resuscitation.2019.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Associations between cardiopulmonary resuscitation (CPR) knowledge, self-efficacy, training history and willingness to perform CPR and CPR psychomotor skills: A systematic review

Abstract: This article is a companion to a systematic review, entitled, Associations between cardiopulmonary resuscitation (CPR) knowledge, self-efficacy, training history and willingness to perform CPR and CPR psychomotor skills: a systematic review (Riggs et al., 2019). The data tables described in this article summarise the impact that specific training interventions, number of times trained, and retention testing intervals have on laypeople's CPR psychomotor skills, as reported by peer-reviewed journal articles. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
90
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(109 citation statements)
references
References 83 publications
6
90
0
3
Order By: Relevance
“…The motivation to perform BLS increases with the number of training sessions [12,[17][18][19][20]. This is because the skill level is associated with selfconfidence [21]. When the youth believe in their own knowledge, they will dare to intervene [17,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The motivation to perform BLS increases with the number of training sessions [12,[17][18][19][20]. This is because the skill level is associated with selfconfidence [21]. When the youth believe in their own knowledge, they will dare to intervene [17,22].…”
Section: Discussionmentioning
confidence: 99%
“…But confidence in performing CPR decreases with the deterioration of skills [23]. Refresher training, which focuses on skills and self-confidence rather than knowledge, should be carried out every 3 months due to the deterioration of skills [21]. It is important to note that individuals with lower self-confidence instead may avoid doing what they are unsure of.…”
Section: Discussionmentioning
confidence: 99%
“…Automated feedback devices leveraging objective performance measures provide real-time audio and visual feedback about performance and lead to improved CPR quality [1,9,12,14,15,19,22]. This feedback increases CPR quality in both training and during actual performance of CPR [12,23,24]. Evidence supports the use of automated real-time visual feedback for developing skill in chest compressions [25,26].…”
Section: Introductionmentioning
confidence: 98%
“…This study is designed to evaluate the hypothesis that VR training is non-inferior to instructor-led training. A recent review reported that the expected effect on compression depth of instructor-led training is about 5 mm, and that the average effect on compression rate is about 17 per minute 29. Data on expected differences in CPR performance in relation to alcohol level are unavailable, but to optimally address this question randomisation will be stratified by alcohol level.…”
Section: Methods and Analysismentioning
confidence: 99%
“…The present study is designed as non-inferiority trial, where the null hypothesis is that VR training is inferior to face-to-face training. The non-inferiority margin for depth is set at 5 mm,29 with an expected SD of 10 mm 30 31. Based on these assumptions, an alpha of 5% and a power of 90%, we calculated that we need 69 participants per group.…”
Section: Methods and Analysismentioning
confidence: 99%